Loading presentation...

Present Remotely

Send the link below via email or IM

Copy

Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

DeleteCancel

Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.
You can change this under Settings & Account at any time.

No, thanks

propiedades fundamentales de las proporciones

No description
by

santiago herreno morales

on 13 November 2013

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of propiedades fundamentales de las proporciones

Propiedad 2 : en toda proporción , la suma o diferencia entre el antecedente y el consecuente de la primera razón es a su antecedente , como la suma o diferencia entre el antecedente y el consecuente de la segunda razón es a su antecedente
Serie de razones iguales : una serie de razones iguales es una igualdad entre dos o más razones .
propiedades fundamentales de las proporciones
Propiedad 3 : en toda proporción, la suma entre el antecedente y el consecuente de la primera razón es a la diferencia entre los mismos , como la suma entre el antecedente y el consecuente de la segunda razón es a la diferencia de los mismos .
Propiedad 4 : en toda serie de razones iguales la suma de los antecedentes es a la suma de los consecuentes , como uno de los antecedentes es a su consecuente .

Propiedad 1 : en toda proporción , la suma o diferencia entre el antecedente y el consecuente de la primera razón es a su consecuente , como la suma o diferencia entre el antecedente y el consecuente de la segunda razón es a su consecuente
a = c → a + b = c + d
b d b d

a = c → a - b = c - d
b d b d

a = c → a + b = c + d
b d a c

a = c → a - b = c - d
b d a c

a = c → a + b = c + d
b d a - b c - d

a = c = e = m
b d f n

a = c = e = m = a + c + e+ m
b d f n b+ d + f+ n

Full transcript